2020
DOI: 10.1155/2020/3293589
|View full text |Cite|
|
Sign up to set email alerts
|

Performance of Distress Thermometer and Associated Factors of Psychological Distress among Chinese Cancer Patients

Abstract: Objective. We aimed to examine the performance of the distress thermometer (DT) and identify the prevalence and risk factors associated with psychological distress (PD) in heterogeneous cancer patients. Methods. This cross-sectional study enrolled 1496 heterogeneous cancer patients from the inpatient and outpatient departments. Receiver operating characteristic analysis (ROC) of DT was evaluated against the Hospital Anxiety and Depression Scale-Total (HADS-T ≥15). An area under the curve (AUC), sensitivity, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 38 publications
(77 reference statements)
2
23
0
Order By: Relevance
“…To meet the need of rapid screening of distress in cancer patients, the single-item Distress Thermometer (DT) was developed by Roth and colleagues for patients to rate distress from 0 ("no distress") to 10 ("extreme distress"). The DT cutoff point has changed slightly in different research [14][15][16][17] . Holland identified 4 as the best cutoff to identify clinical distress in a cancer patient, 14 and the NCCN Clinical Practice Guidelines for Distress Management recommends using a DT cutoff score of 4 followed by a Problem List (PL) to investigate any unmet psychological needs in the prior week.…”
Section: Introductionmentioning
confidence: 99%
“…To meet the need of rapid screening of distress in cancer patients, the single-item Distress Thermometer (DT) was developed by Roth and colleagues for patients to rate distress from 0 ("no distress") to 10 ("extreme distress"). The DT cutoff point has changed slightly in different research [14][15][16][17] . Holland identified 4 as the best cutoff to identify clinical distress in a cancer patient, 14 and the NCCN Clinical Practice Guidelines for Distress Management recommends using a DT cutoff score of 4 followed by a Problem List (PL) to investigate any unmet psychological needs in the prior week.…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies have shown that people with cancer experience intense suffering resulting from chemotherapy (Brandl et al, 2019; Thapa et al, 2020). Evaluating this phenomenon is important, not only in epidemiological studies, but also for the clinical practice of professionals who daily witness the pain experienced by these patients.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have addressed this phenomenon by means of specific screening instruments, conjecturing that suffering is a complex human response that encompasses physical, psychological, social, and spiritual aspects (Mendonça, Pereira, Magnago, Silva, et al, 2020b; Rajeshwari et al, 2020; Thapa et al, 2020), others have treated it analytically by using measures of anxiety and depression, interpreting it in terms of psychiatric morbidity (El Kheir & Ibrahim, 2019; Lu et al, 2019; McMullen et al, 2018; Wen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the article titled “Performance of Distress Thermometer and Associated Factors of Psychological Distress among Chinese Cancer Patients” [ 1 ], Dr. Ahmad Khalid Aalemi was missing from the authors' list. Dr. Aalemi shared his knowledge and experience during the study design, data cleaning, data analysis, and report writing.…”
mentioning
confidence: 99%